BIG FIVE PERSONALITY TRAITS AND RECIPROCAL RELATIONSHIP BETWEEN JOB SATISFACTION AND JOB PERFORMANCE - Purwanto; Halim, Liany; Yanuar R Syah, Tantri; Haizam Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This journal was created with the aim of connecting the relationship between three variables related to human resource management in a company, namely personality traits, job satisfaction and job performance. This model was developed to build a hypothesis on how personality can increase job satisfaction and job performance and influence between job satisfaction and job performance. The survey was conducted from October 2019 to January 2020 through a google form. As many as 485 data were collected which were then validated. The model values using Lisrel 8.7. This study contributes to add to the compilation of findings, so as to clarify the causes of inconsistencies in previous findings between the relationship of personality characteristics that most influence with job satisfaction and performance.